Effect of ion irradiation on the surface energy of deposited coatings - Eremin, E. N.; Guchenko, S. A.; Kasymov, S. S.; Yurov, V. M.; Vedyashkin, M. V. (IOP PUBLISHING LTD, 2017)
We investigated multi-element coatings exposed to argon ion bombardment. The coatings were irradiated using a multi-ampere hollow-cathode ion source. The arc current was 1 A, and the potential of the substrate was maintained equal to 300 V. The surface tension (surface energy) of the coatings was measured before and after irradiation through the size-dependence of the microhardness and electrical resistivity of coatings on their thickness. Ion irradiation was found to affect the surface energy of the coatings in different ways. This is due to both the structure of the coating and its elemental composition.